A systematic review of flurbiprofen 8.75 mg dose and risk of adverse events (excluding haemorrhagic) resulting from drug-drug interactions - Evans, Alison; Roy, Debabrata; Dhanda, Sandeep; Lane, Samantha; Coutinho, Graça; Kulasekaran, Anuradha; Miller-Shakesby, David; Ramamoorthi, Nagalakshmi; Shakir, Saad (Frontiers in Pharmacology, 2024)
Background: Flurbiprofen 8.75mg lozenges and oromucosal sprays are used for symptomatic relief of sore throat in patients aged 12 years and over. The documented adverse events of flurbiprofen use include those related to its pharmacological actions, namely increased risk of haemorrhagic events, however other adverse events (such as nephrotoxicity and cardiac failure) have been known to occur. The likelihood of occurrence of adverse events increases when flurbiprofen is used concomitantly with some other medications. Therefore, the objective of this systematic review was to collate the current evidence on adverse events which occur with flurbiprofen 8.75mg dose (any formulation), in particular as a result of interaction with other medicinal products, with a focus on non-haemorrhagic events. Methods: Systematic searches of the literature were conducted to identify literature on any formulation of flurbiprofen 8.75 mg up to the date of the electronic database search (data lock: 28th April 2020). Publications were screened to identify studies reporting non-haemorrhagic adverse events with flurbiprofen 8.75mg and/or non-haemorrhagic adverse events in the comparator arm. Data extraction was performed for eligible studies according to pre-defined criteria and summarised in narratives, tables and figures. Risk of bias and certainty of evidence assessments were planned for each included study where results relating to the primary objective of the systematic review were available. Results: Of 1528 publications identified by systematic literature searches, 26 met the inclusion criteria and were included in this review. None of these 26 studies contained information on non-haemorrhagic adverse events occurring as a result of a drug-drug interaction (interaction with concomitant medication used with flurbiprofen 8.75mg), as per the primary objective and secondary objectives of the systematic review. Conclusion: Results from this systematic review on the risk of non-haemorrhagic events did not provide evidence for these events occurring as a result of interaction with other medicinal products. Additional appropriately designed studies would be required to confirm whether these findings suggest a true absence of risk or limitations in reporting.